2014
DOI: 10.1002/cbin.10242
|View full text |Cite
|
Sign up to set email alerts
|

NecroX‐5 suppresses sodium nitroprusside‐induced cardiac cell death through inhibition of JNK and caspase‐3 activation

Abstract: Although sodium nitroprusside (SNP) is an effective hypotensive drug and is often used in pediatric intensive care units and to treat acute heart failure, clinical application of SNP is limited by its cardiotoxicity. NecroX-5 (NX-5) was recently developed and has the capacity to inhibit necrotic cell death. No current literature addresses whether NX-5 suppresses SNP-induced cell death or its mechanism of action. We have investigated the protective role of NX-5 against SNP-induced cell death in cardiomyocyte-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…It has been suggested that the mitochondria serve as a metabolizer and target of nitrite, a nitric oxide metabolite (Shiva, ), and influence the responses to environmental pollutants, or drugs (Meyer et al, ). Therefore, we tested the toxicity of an excess of sodium nitroprusside (Lee et al, ), an exogenous nitric oxide donor in naïve H9c2 cells and H9c2 rho(0) cells. As shown in Figure A, 2 mM sodium nitroprusside caused severe cellular in naïve H9c2 cells while H9c2 rho(0) cells were highly resistant against same concentrations of the insult.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that the mitochondria serve as a metabolizer and target of nitrite, a nitric oxide metabolite (Shiva, ), and influence the responses to environmental pollutants, or drugs (Meyer et al, ). Therefore, we tested the toxicity of an excess of sodium nitroprusside (Lee et al, ), an exogenous nitric oxide donor in naïve H9c2 cells and H9c2 rho(0) cells. As shown in Figure A, 2 mM sodium nitroprusside caused severe cellular in naïve H9c2 cells while H9c2 rho(0) cells were highly resistant against same concentrations of the insult.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in the levels of Bcl‐2 in H9c naïve and H9c2 rho(0). Anti‐apoptotic Bcl‐2 inhibits mitochondria‐driven cell death and this reduction of Bcl‐2 is induced in sodium nitroprusside mediated cell death (Lee et al, ). In line with this, the result from Figure B showed that the reduction of Bcl‐2 by sodium nitroprusside insult was highly suppressed in H9c2 rho(0) cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant improvement in the protection of cell and tissue has been showed against various injury factors, such as neomycin, nitroprusside, oxidative stress, and gentamicin [5][6][7]. Recently, the fundamental role of NecroX-5 in IRI in the heart and liver has been described, however, there has been no research to determine the molecular mechanisms underlying the inhibition of NecroX-5 in IRI [8,9].…”
Section: Original Articlementioning
confidence: 99%